Media use among adolescents with autism spectrum disorder. (November 2014) - Kuo, Melissa H; Orsmond, Gael I; Coster, Wendy J; Cohn, Ellen S
This study explores how adolescents with autism spectrum disorder (ASD) use media, and the factors associated with their media use. A total of 91 adolescents with ASD and their parents completed mail-based surveys. In all, 78% of the adolescents with ASD watched television (approximately 2 h/day), and 98% used computers (approximately 5 h/day) on any given day. They most frequently watched cartoons, played computer or video games that involved shooting, and visited websites that contained information on video games. Adolescents with ASD who watched television with parents reported more positive parent–child relationships. Adolescents with ASD who visited social networking websites or received emails from friends reported more positive friendships. The findings help us understand media-use habits of adolescents with ASD and suggest areas for future research.